SYNTHESIS AND CHARACTERIZATION OF SCHIFF BASE TRANSITION METAL COMPLEXES - Ibraheem, Hanan Abd El-Latif (Al-Nahrain Journal of Science, 2009)
New metal complexes of cu(II); Ni(II); Co(II); Mn(II); Zn(II); VO(IV) and Cd (II) have been synthesized from the Sciff base (L) derived from 4-amino antipyrine,salicyaldehyde and O-phenylene diamine. The prepared complexes where characterized by magnetic susceptibility, Molar conductance,FTIR,Uv-vis. The data show that these complexes have composition of ML type. The uv-vis,magnetic susceptibility data of the complexas suggest asquare-planar geometry around the central metal ion except VO(IV )complex which has square-pyramidal geometry.